2015
DOI: 10.1038/srep07912
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin induces ischemic LTP (iLTP): implications for synaptic plasticity in the acute phase of ischemic stroke

Abstract: Acute brain ischemia modifies synaptic plasticity by inducing ischemic long-term potentiation (iLTP) of synaptic transmission through the activation of N-Methyl-D-aspartate receptors (NMDAR). Thrombin, a blood coagulation factor, affects synaptic plasticity in an NMDAR dependent manner. Since its activity and concentration is increased in brain tissue upon acute stroke, we sought to clarify whether thrombin could mediate iLTP through the activation of its receptor Protease-Activated receptor 1 (PAR1). Extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 48 publications
(74 reference statements)
2
73
0
2
Order By: Relevance
“…It has been reported that thrombin, plasmin and kallikrein promote neuron injury and exacerbate glutamate neurotoxicity directly or indirectly [5,6]. For instance, thrombin induces ischemic long-term potentiation (LTP) in hypoxia-treated neurons, impairs the normal LTP [7] and perturbs neurite outgrowth; plasmin contributes to ischemia-induced neuron death [8]; and kallikrein 6 exacerbates glutamate neurotoxicity, implying that serine proteases could be potential targets for neuro-protection following stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thrombin, plasmin and kallikrein promote neuron injury and exacerbate glutamate neurotoxicity directly or indirectly [5,6]. For instance, thrombin induces ischemic long-term potentiation (LTP) in hypoxia-treated neurons, impairs the normal LTP [7] and perturbs neurite outgrowth; plasmin contributes to ischemia-induced neuron death [8]; and kallikrein 6 exacerbates glutamate neurotoxicity, implying that serine proteases could be potential targets for neuro-protection following stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in brain slices that are subjected to ischemic conditions such as OGD, no circulating coagulation factors are involved and the time points examined were somewhat shorter. Thrombin that is generated in the brain cells rises (14, 15) and as a result PAR1, its own receptor, may first increase as a complementary step, but these receptors are then cleaved and internalized leading to reduced levels. It is hypothesized that inhibiting the levels of thrombin during acute stroke will normalize PAR1 levels at the 2–24 hour time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this receptor by low concentrations of thrombin may have neuroprotective effects, while at higher concentrations thrombin has deleterious effects (711). In the setting of an acute ischemic stroke, high thrombin levels have been detected in the infarct area, possibly as a consequence of blood–brain barrier opening (12, 13) or as a result of its local synthesis in the brain (14, 15) or both. Functionally, thrombin has been shown to cause synaptic dysfunction (1519) and later, on vascular disruption, inflammatory response and neuronal damage (2022), through the activation of PAR1 (13, 20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of prothrombin mRNA expression and thrombin activity have been detected in brain tissue after acute ischemic stroke (36, 37). In addition, thrombin has been shown to cause synaptic dysfunction, and thrombin activity was associated with neuronal damage (38, 39). Furthermore, thrombin-dependent fibrin deposition and platelet activation can lead to microvascular thrombosis during both the ischemia and reperfusion phase, leading to the expansion of the initial infarct.…”
Section: Discussionmentioning
confidence: 99%